COMPARISON OF CONVENTIONAL PAP SMEAR AND LIQUID-BASED CYTOLOGY IN DETECTING CERVICAL ABNORMALITIES - Šečerović, Đelila (Sanamed, 2024)
Cervical cancer represents one of the most common types of cancer in women, requiring early diagnosis to reduce prevalence and mortality rates. The Pap smear plays a crucial role in the early diagnosis of precancerous lesions. While the conventional Pap smear has been the standard method for lesion detection, liquid-based cytology (LBC) is emerging as an alternative with potential advantages. Research comparing the conventional Pap smear to LBC has shown that LBC yields a higher percentage of satisfactory samples and demonstrates greater sensitivity and specificity in identifying various cervical abnormalities. Similar findings have been reported in Japanese research. However, some studies have shown conflicting results, emphasizing the specificity of the conventional method. While some studies suggest that the conventional Pap smear is better at detecting ASC-US, others show similar or favorable results for the LBC method. The LBC method stands out for its higher diagnostic sensitivity, especially in detecting various types of cervical abnormalities, while the conventional Pap smear method maintains its specificity, particularly in diagnosing LSIL. The LBC method has the advantage of better sample representativeness and fewer unsatisfactory samples.